2015
DOI: 10.5194/soild-2-29-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of fresh and aged biochars from pyrolysis and hydrothermal carbonization on nutrient sorption in agricultural soils

Abstract: Abstract. Leaching of nutrients from agricultural soils causes major environmental problems that may be reduced with biochar amendments to the soils. Biochars are characterised by a high adsorption capacity, i.e., they may retain nutrients such nitrate and ammonium. However, biochar properties strongly depend on feedstock and the production process. We investigated the nutrient retention capacity of biochars derived from pyrolysis (pyrochar) as well as from hydrothermal carbonization (hydrochar; produced at 20… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Sugarcane filter‐cake BC, produced at >500°C, reduced dissolved organic carbon (DOC) but not NO 3 − leaching from a sugarcane field treated with vinasse (nutrient‐dense effluent containing 0.08 g N L −1 ) (Eykelbosh et al, 2015). Biochar from woodchips significantly increased mineral nitrogen (N min ) (NO 3 − , NH 4 + ) and phosphate retention in a laboratory study, whereas the same BC lost 60 to 80% of adsorption capacity after 7 mo of field incubation (Gronwald et al, 2015).…”
mentioning
confidence: 99%
“…Sugarcane filter‐cake BC, produced at >500°C, reduced dissolved organic carbon (DOC) but not NO 3 − leaching from a sugarcane field treated with vinasse (nutrient‐dense effluent containing 0.08 g N L −1 ) (Eykelbosh et al, 2015). Biochar from woodchips significantly increased mineral nitrogen (N min ) (NO 3 − , NH 4 + ) and phosphate retention in a laboratory study, whereas the same BC lost 60 to 80% of adsorption capacity after 7 mo of field incubation (Gronwald et al, 2015).…”
mentioning
confidence: 99%
“…In particular, CO 2 and N 2 O add to the global warming potential, whilst NH 3 and P leaching contribute to eutrophication (ibid.). The fact that biochar captures NO 3and PO 4 3-, as shown, for example, by Agyarko-Mintah et al 2016, Gronwald et al (2015) and Kammann et al (2015), is promising in regard to reducing GHG emissions and nutrient leaching during composting and also after compost is added to the soil. There is also empirical evidence that adding biochar to composting can decrease N 2 O and CH 4 emissions (e.g.…”
Section: The Effects Of Composting Biochar On Environmental Emissionsmentioning
confidence: 96%
“…In addition, biochar additions to composting can potentially decrease N 2 O and CH 4 emissions, e.g., [86][87][88][89], whilst NH 3 emissions potentially increase (e.g., [87]). Other studies [33,90] showed that biochar captures nitrate and phosphate during composting, which is promising, in order to reduce nutrient leaching. However, such potentially beneficial effects of co-composting biochar have not yet been included in our model (Section 3.5).…”
Section: Environmental Emissionsmentioning
confidence: 99%